A new chapter in the housing development industry / Mahamat Ibrahim - Ibrahim, Mahamat (Faculty of Accountancy, 1991)
This study describes the problems foreseen by housing developers as a result of the enactment of the Housing Developers (Control and Licensing) (Amended) Act, 1988. The Housing Developers Association has expressed concern that the associated problems would restrict the expansion of housing development companies and may stifle the housing industry's ability to grow further.